Non-verbal communication questionnaire: a measure to assess effective interaction - Khan, Maryam; Zeb, Sana; Batool, Rabia; Gasiorowska, Agata (Frontiers in Psychology, 2025)
In five studies, we document the development and validation of the Non-verbal Communication Questionnaire (NVCQ). This eight-item measurement tool assesses how people perceive non-verbal cues across two dimensions of effective communication. These two dimensions, encouraging and discouraging non-verbal cues, are based on Khan and Zeb's (2021) version of the 10-part model of non-verbal communication. Study 1 reports the development of the NVCQ and provides initial support for the factorial structure of the measure in a Pakistani sample. Studies 2 and 3 confirmed the factorial structure and demonstrated the construct validity of the NVCQ. A preregistered Study 4 confirmed the factorial structure in a Polish sample, and provided additional support for the construct validity of the measure, while Study 5 demonstrated its adequate test–retest reliability. We conclude that the NVCQ is a psychometrically sound instrument for assessing effective communication that incorporates non-verbal aspects in every domain of life, from clinical to research settings.